High Conduction Hopping Behavior Induced in Transition Metal Dichalcogenides by Percolating Defect Networks: Toward Atomically Thin Circuits. (1st August 2017) - Stanford, Michael G.; Pudasaini, Pushpa R.; Gallmeier, Elisabeth T.; Cross, Nicholas; Liang, Liangbo; Oyedele, Akinola; Duscher, Gerd; Mahjouri‐Samani, Masoud; Wang, Kai; Xiao, Kai; Geohegan, David B.; Belianinov, Alex; et al.
Abstract : Atomically thin circuits have recently been explored for applications in next‐generation electronics and optoelectronics and have been demonstrated with 2D lateral heterojunctions. In order to form true 2D circuitry from a single material, electronic properties must be spatially tunable. Here, tunable transport behavior is reported which is introduced into single layer tungsten diselenide and tungsten disulfide by focused He + irradiation. Pseudometallic behavior is induced by irradiating the materials with a dose of ≈1 × 10 16 He + cm −2 to introduce defect states, and subsequent temperature‐dependent transport measurements suggest a nearest neighbor hopping mechanism is operative. Scanning transmission electron microscopy and electron energy loss spectroscopy reveal that Se is sputtered preferentially, and extended percolating networks of edge states form within WSe2 at a critical dose of 1 × 10 16 He + cm −2 . First‐principle calculations confirm the semiconductor‐to‐metallic transition of WSe2 after pore and edge defects are introduced by He + irradiation. The hopping conduction is utilized to direct‐write resistor loaded logic circuits in WSe2 and WS2 with a voltage gain of greater than 5. Edge contacted thin film transistors are also fabricated with a high on/off ratio (>10 6 ), demonstrating potential for the formation of atomically thin circuits. Abstract : Percolating networks of defects are introduced into WSe2 and WS2 to tune the transport behavior. Pseudometallic behavior is induced at a particular defect concentration, and temperature‐dependent transport measurements suggest a nearest neighbor hopping mechanism is operative. The high conduction behavior, induced by percolating networks of defects, is used to create resistor loaded logic circuits and edge contacted transistors.